2020
DOI: 10.3389/fmicb.2020.590370
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Transplant in the Treatment of Obesity and Diabetes: Current and Future Perspectives

Abstract: A wealth of evidence has revealed the critical role of the gut microbiota in health and disease. Many chronic diseases have been associated with gut microbiota imbalance in its composition, diversity and functional capacity. Several types of interventions have been shown to correct microbiota imbalance and restore the beneficial metabolic outcomes of a normal microbiota. Among them, fecal microbiota transplantation (FMT) is an emergent, promising technology employed to improve clinical outcomes of various path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 103 publications
(231 reference statements)
0
33
0
1
Order By: Relevance
“…Moreover, we found that PDX treatment significantly modulated the gut microbiota structure in obese mice. Previous studies have indicated that gut microbiota dysbiosis is one of the reasons for obesity and related disorders, and fecal microbial transplantation (FMT) is considered a potential source of novel therapeutics (Napolitano and Covasa, 2020;He et al, 2021;Voland et al, 2021). FMT from the obesity-associated human gut microbiota to mice can induce vascular dysfunction and glucose intolerance, and FMT from lean donors to patients with obesity can promote metabolic benefits (Mocanu et al, 2021;Russo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that PDX treatment significantly modulated the gut microbiota structure in obese mice. Previous studies have indicated that gut microbiota dysbiosis is one of the reasons for obesity and related disorders, and fecal microbial transplantation (FMT) is considered a potential source of novel therapeutics (Napolitano and Covasa, 2020;He et al, 2021;Voland et al, 2021). FMT from the obesity-associated human gut microbiota to mice can induce vascular dysfunction and glucose intolerance, and FMT from lean donors to patients with obesity can promote metabolic benefits (Mocanu et al, 2021;Russo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies showed a promising beneficial effect of FMT, manifested by improved insulin sensitivity, glycemic control, and reduced chronic systemic inflammation [159]. However, high-quality well-powered RCTs with longer follow-up are urgently needed to highlight the benefits of FMT as a viable option for patients with obesity and metabolic syndrome in the future.…”
Section: Metabolic Syndrome/obesitymentioning
confidence: 99%
“…Outside the context of hematologic and oncologic conditions, FMT has been used to regulate host metabolism in both animal models of obesity [18,19] and in obese humans [20,21]. FMT from lean donors resulted in variable improvements in the insulin-sensitivity in obese recipients [22,23] and in patients with metabolic syndromes [22,23]. Improvement was associated with an increased abundance of butyrate-producing intestinal microbes.…”
Section: Biologic Consequences Of Fmtmentioning
confidence: 99%